Load absorption force-time characteristics following the second pull of weightlifting derivatives - Suchomel, T. J.; Lake, J. P.; Comfort, P. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to compare the load absorption force-time characteristics of weightlifting catching and pulling derivatives. Twelve resistance-trained men performed repetitions of the hang power clean (HPC), jump shrug (JS), and hang high pull (HHP) on a force platform with 30, 45, 65, and 80% of their 1-repetition maximum HPC. Load absorption phase duration, mean force, and work were calculated from the force-time data. The HHP produced a significantly longer load absorption phase duration compared with the HPC (p < 0.001; d = 3.77) and JS (p < 0.001; d = 5.48), whereas no difference existed between the HPC and JS (p = 0.573; d = 0.51). The JS produced significantly greater load absorption mean forces compared with the HPC (p < 0.001; d = 2.85) and HHP (p < 0.001; d = 3.75), whereas no difference existed between the HPC and HHP (p = 0.253; d = 0.37). Significantly more load absorption work was performed during the JS compared with the HPC (p < 0.001; d = 5.03) and HHP (p < 0.001; d = 1.69), whereas HHP load absorption work was also significantly greater compared with the HPC (p < 0.001; d = 4.81). The weightlifting pulling derivatives examined in the current study (JS and HHP) produced greater load absorption demands after the second pull compared with the weightlifting catching derivative (HPC). The JS and HHP may be used as effective training stimuli for load absorption during impact tasks such as jumping.